2017
DOI: 10.3390/s17122948
|View full text |Cite
|
Sign up to set email alerts
|

Blind Compensation of I/Q Impairments in Wireless Transceivers

Abstract: The majority of techniques that deal with the mitigation of in-phase and quadrature-phase (I/Q) imbalance at the transmitter (pre-compensation) require long training sequences, reducing the throughput of the system. These techniques also require a feedback path, which adds more complexity and cost to the transmitter architecture. Blind estimation techniques are attractive for avoiding the use of long training sequences. In this paper, we propose a blind frequency-independent I/Q imbalance compensation method b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A review of methods [25][26][27][28][29][30][31][32] for estimating the channel and signal distortion in a direct conversion receiver showed that most often, the estimation of IQ imbalance is considered, or high-precision procedures for joint estimation of channel parameters and signal distortion, such as IQ imbalance, frequency shift, and DC offset, which have a very high computational complexity [32]. Known algorithms work either according to special test sequences [29][30][31] or "blindly" [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of methods [25][26][27][28][29][30][31][32] for estimating the channel and signal distortion in a direct conversion receiver showed that most often, the estimation of IQ imbalance is considered, or high-precision procedures for joint estimation of channel parameters and signal distortion, such as IQ imbalance, frequency shift, and DC offset, which have a very high computational complexity [32]. Known algorithms work either according to special test sequences [29][30][31] or "blindly" [33].…”
Section: Introductionmentioning
confidence: 99%
“…This means that this approach requires the transmission of a test signal again. For example, in [25] the statistical properties of the channel are known, in [26] it is necessary to know the joint PDF of the signal components. In [27], joint estimation and compensation of IQ imbalance are considered.…”
Section: Introductionmentioning
confidence: 99%
“…example [6]), to the best of our knowledge, it has not been investigated for 5G, despite its severity in mmWave systems [7]. IQI gain and phase parameters are usually compensated during the channel estimation phase [6], [8]. In mmWave systems, this is the phase during which DOD, DOA, and TOA are estimated and ultimately a position fix is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of IQ imbalance (IQI) on positioning was studies previously in several papers (See for example [6]), to the best of our knowledge, it has not been investigated for 5G, despite its severity in mmWave systems [7]. IQI gain and phase parameters are usually compensated during the channel estimation phase [6], [8]. In mmWave systems, this is the phase during which DOD, DOA, and TOA are estimated and ultimately a position fix is obtained.…”
Section: Introductionmentioning
confidence: 99%